Identification Method for Flexure and Shear Behavior of Cantilever Structures - F. Garcés; C. Genatios; P. García; A. Mebarki; M. Lafuente (Shock and Vibration)
This article presents an original identification method for the assessment of flexure and shear stiffness of cantilever structures or shear wall buildings. Required data include an initial (theoretical) model, an estimation of lumped mass values (by floor) and an experimental evaluation of two eigenvalues (modal frequencies and their modal shapes). The method estimates coefficients whenever flexural (EI) or shear (GA) values are relevant or irrelevant. An initial formula includes both shear and flexural components. Furthermore, particular developments are carried out for particular cases of irrelevant shear or flexural deformations. A numerical simulation of a real chimney is performed to study the effectiveness of the methodology in identifying damage under noise conditions. A dynamic-test experiment is carried out on a steel cantilever which suffers damage in two sections. The result obtained from the application of the proposed methodology is satisfactory in both numerical and experimental cases, identifying precisely the stiffness changes in the system.